2012
DOI: 10.1055/s-0032-1320031
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Lumbar Disc Herniation after Microendoscopic Discectomy

Abstract: The recurrence rate and reoperation rate for LDH after MED were comparable to those of conventional discectomy. More than half of the cases of recurrence occurred at an early postoperative phase, and patients with caudally migrated LDH experienced recurrence significantly more often than those with rostrally migrated or nonmigrated LDH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 19 publications
1
27
1
3
Order By: Relevance
“…Highly successful results have been obtained with lumbar disc surgery, but 2.8-24 % of patients undergo reoperations after their primary surgery [1][2][3][4][5][6][7]. The most common cause of lumbar disc reoperation has been reported to be reherniation [5,[7][8][9], which includes real recurrent herniation [7] (homolateral herniation at the same level), contralateral herniation at the same disc level and new herniation at another level. The following discectomy-related conditions can also occasionally give rise to revision surgery: scar, adhesive arachnoiditis, infection, epidural haematoma, pseudomeningocele, and other complications [1,7,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Highly successful results have been obtained with lumbar disc surgery, but 2.8-24 % of patients undergo reoperations after their primary surgery [1][2][3][4][5][6][7]. The most common cause of lumbar disc reoperation has been reported to be reherniation [5,[7][8][9], which includes real recurrent herniation [7] (homolateral herniation at the same level), contralateral herniation at the same disc level and new herniation at another level. The following discectomy-related conditions can also occasionally give rise to revision surgery: scar, adhesive arachnoiditis, infection, epidural haematoma, pseudomeningocele, and other complications [1,7,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…There are several risk factors for recurrence of a herniated disc. In some studies, age differences (15,16) and gender (1) have been reported as a risk factor for recurrence of the herniated disc while other studies reported that age and gender did not relate to a higher recurrence rate (17)(18)(19)(20). There was no significant difference in age and gender between the groups with and without recurrence which open microdiscectomy was performed in re-operation (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 183 patients had severe lumbar disc herniation with damage to annulus fibrosus or protrusion and extrusion types, which are usually considered contraindications to PLD [17, 18]. After treatment, an effective rate of 92.9% was achieved which was comparable with open surgery [19, 20]. Therefore, our data indicated that PLLD, as a minimally invasive treatment, may be effective in treating some severe lumbar disc herniation, lumbar disc prolapse, and spinal stenosis caused by disc bulge.…”
Section: Discussionmentioning
confidence: 99%